Youth and reconciliation - Samant, Erin; Rhead, Daxton (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2017)
On Monday, March 6, 2017, students from Glebe Collegiate organized a demonstration on the steps of Parliament Hill in Ottawa, Ontario. The students called on the Prime Minister and other elected officials to treat Indigenous peoples with dignity and respect and to immediately cease discriminatory practices. The students named this event Youth and Reconciliation. Erin Samant and Daxton Rhead helped organize and lead Youth and Reconciliation. What follows is a transcript of their statements to fellow students, allies, Members of Parliament, and Indigenous organizations that were present during the event.